'Doing it for real now' – The transition from healthcare assistant to newly qualified nurse: A qualitative study. (July 2018) - Draper, Jan
Abstract: Background: There has been increasing international research and policy interest concerning the transition from student to newly qualified nurse (NQN). However, the influence of previous employment as a healthcare assistant (HCA) on students' experiences of this transition is comparatively under-researched. Aims and Objectives: To explore the experiences of NQNs also employed as HCAs during their pre-registration education programme and how this prior and ongoing HCA experience influenced their transition experiences. Design: Qualitative research design using a descriptive method. Setting and Participants: Former students ( n = 14) of a unique four year, part-time, employer-sponsored pre-registration nursing programme, specifically designed for HCAs and delivered by supported open learning, located in different regions and nations of the United Kingdom who had qualified within the last two years. Methods: Telephone interviews, digitally recorded, transcribed verbatim and analysed using NVivo8. Results: Four themes described participants' experiences of transition: In at the deep end, Changing identities, Coming together and Scaffolding . Findings confirm existing literature that all NQNs appear to experience a similar overarching experience of transition, including those with prior HCA experience. However, familiarity with people, place and routines afforded by this previous experience appeared to ease transition, particularly if the NQNs stayed in their previous HCA work location. However, managing the dual roles of being both HCA and student and adapting to their changing identities were frequently cited as particular challenges. Conclusions: Van Gennep's Rites de Passage and Bridge's work on organisational change were combined to theoretically analyse participants' accounts of transition. This illustrated that transition is not always linear with clearly defined and bounded stages but can also be seen as a more undulating or organic process with curving, slanting and overlapping phases. NQNs can therefore simultaneously occupy more than once phase in their journey of transition. Implications for students, higher education and practice are highlighted. Highlights: There is an overarching transition to NQN experience, including former HCAs. Knowledge of people, places and routines as an HCA assisted transition. The dual roles of being both HCA and student created some tensions. Transition is complex and is not necessarily a linear but a more organic process.